Contraceptive use and associated factors among female adolescents living in Katwe – Butego Division, Masaka District, Uganda: A cross-sectional study. - Nabimanya, Edward; Nakidde, Dr. Gladys; Tweheyo, Dr .Anne Otwine; Tukirinawe, Happy; Wasswa, Bright; Matovu, Daneil; Arinaitwe, Elizabeth; Atwikirize, Vastine (Student's Journal of Health Research Africa, 2025)
Background The study aims to assess the factors associated with contraceptive use among adolescents in Masaka district. Methods A cross-sectional study design incorporating both quantitative and qualitative approaches was employed. The study targeted 6,338 female adolescents aged 15–24 years. Using proportionate sampling, 90 adolescents were selected from Butego parish and 97 from Katwe parish. Data was analyzed using STATA version 17. Descriptive statistics were used to determine contraceptive use prevalence, while binary logistic regression identified factors associated with use. Findings The results show that 51.9% of the respondents were from Katwe Parish, while 48.1% were from Butego Parish, and the majority were married (64.7%. Most respondents were aged between 15 and 19 years (72.7%), while a smaller proportion were aged between 10 and 14 years (27.3%). Of the 187 female adolescents, 62% were using contraceptives. The married female adolescents were 3.9 times more likely to use contraceptives than single adolescents (AOR = 3.987; 95% CI: 1.528–10.407; p = 0.005). Divorced or separated adolescents had lower odds of using contraceptives than their single counterparts(AOR = 0.018; 95% CI: 0.001–0.597; p = 0.024). Adolescents who had ever faced challenges in affording contraceptives had significantly higher odds of contraceptive use compared to those who had never faced such challenges (AOR = 51.130; 95% CI: 5.777–452.553; p = 0.000. Conclusion For every 10 adolescents, 6 are using contraceptives. Potential health risks associated with contraceptive methods, and whether adolescents had ever faced challenges in affording contraceptives, were key factors associated with contraceptive use among female adolescents. A low contraceptive uptake was higher among single adolescents. Recommendation Targeted outreach programs through communities, youth clubs, and social media should focus on educating and encouraging this group to seek reproductive health services.